Mediating reconciliation with God: Exploring divine forgiveness experiences during confession among Catholic priests from four Spanish-speaking countries - Carmen Callizo; Martiño Rodríguez-González; María Calatrava; María Pilar Martínez-Díaz; Kaye Cook; Richard G. Cowden (PLoS ONE, 2026)
Divine forgiveness (DF), the subjective experience of being forgiven by a higher power after a transgression, remains understudied in psychology, particularly across diverse cultural and religious contexts. This study examines priests’ experiences and understandings of DF, both as confessors and penitents, in the Catholic Sacrament of Confession through semi-structured interviews with ten Spanish-speaking priests from Spain, Mexico, Peru, and Chile. Guided by a constructivist stance and a Christian-sensitive relational spirituality model of personal sin, we conducted a theory-informed framework analysis combining inductive coding with iterative matrix-based synthesis. Findings showed that 1) confession emerged as a relational and dynamic encounter involving the self, sin, God, others, and the confessor, whose mediating role makes DF tangible; 2) DF unfolded across phases of vulnerability, repentance, confession, penance, and absolution; 3) barriers included guilt, shame, and scrupulosity, whereas facilitators involved empathetic priestly presence and communal support; and 4) participants distinguished between cognitive certainty of DF and its emotional realization enabled by the confessor’s presence. These findings provide preliminary, contextually grounded insights related to both Christian-sensitive and faith-neutral models of DF, which should be further examined and empirically tested in future research.